Analysis of the Buddhist Concept of Economics in Theravada Buddhism (Pashupati Pragya पशुपति प्रज्ञा, 2025)
The study's goal is to describe sociological methods for analyzing the Buddhist concept of Economics in Theravada Buddhism. Buddhist studies have not thoroughly examined Buddhist communities' economic institutions, as well as the strategies and techniques used to meet their needs for resources. Buddhist studies focus primarily on its religious, philosophical, political, and cultic dimensions, with little to no attention paid to its economics. Along with this, Buddhism served crucial economic purposes. They were the focus of several Western scholars' research. They established the framework for the growth of the Buddhist economy's scientific tendencies. In the development of sociology, various theories can be highlighted. Within their framework, issues of the influence of Buddhism on economic development were investigated. The article tries to describe the economic roles of Buddhist teaching institutions and expose key elements of the theoretical analysis of the economy in Buddhist communities. Three theoretical models of the Buddhist economy that had disparate effects on science and competed at times were described as a consequence of the investigation. This study takes into account Weber and Marxist writings as well as their understanding of the economic impact of Buddhism. The role M. Weber played in the advancement of Buddhism.